Management of Facilities and Infrastructure in Improving The Learning Process of Students at Diniyah Takmiliyah Awwaliyah Al-Furqon - Putri, Dewi Amanada (JIEM (Journal of Islamic Education Management), 2021)
The facilities and infrastructure owned by Diniyah Takmiliyah Awwaliyah Al-Fur-qon Paniis Village can be said to be lacking because there is still a shortage of classrooms in learning, there are still those who study in the prayer room.  In fulfilling the facilities in the classroom, learning activities are very influential for students such as the completeness of tools and preparation for learning. The management of facilities and infrastructure in improving the learning process in Diniyah Takmiliyah Awwaliyah Al-Fur-qon Paniis Village includes planning, organizing, procurement and supervision.  To conduct a selection of the items to be used, it means that the manager checks the items that support the learning process, to avoid unwanted mistakes. The teacher's efforts are made to improve the learning process of students at Diniyah Takmiliyah Awwaliyah Al-Fur-qon Paniis Village, the teacher's obstacles in improving the learning process of students are limited facilities and infrastructure that are less supportive, problems for students can also be seen from their family factors  themselves, because most of them do not live with their parents but with their grandparents, so the lack of parental supervision and upbringing is like student discipline, resulting in obstacles in improving the learning process in madrasas. Supporting and inhibiting factors in improving the learning process of students in Diniyah Takmiliyah Awwaliyah Al-Fur-qon Paniis Village, as for the supporting factors, one of which is the teacher, the teacher's role is very important for the learning process, because professionalism will determine success during the learning process.  teaching and learning in the classroom.  Meanwhile, environmental problems in the inhibiting factors of the learning process usually occur in students, namely the lack of interest of students in the learning process.  This is because it was found that some students were still outside while studying, while in the classroom there were still noise, there were also students who were nosy with their friends in the class.  The process of increasing at Al-Furqon DTA can be seen from the number of students who enter every year.Keywords: Management of Facilities and Infrastructure, Learning Process Sarana dan prasarana yang di miliki Diniyah Takmiliyah Awwaliyah Al-Fur-qon Desa Paniis dapat                 dikatakan kurang karena masih kekurangan  ruang kelas dalam pembelajaran, masih ada yang belajar di mushola. Dalam pemenuhan sarana di dalam kelas kegiatan pembelajaran sangat berpengaruh bagi peseta didik seperti kelengkapan alat dan persiapan pembelajaran. Pengelolaan  sarana dan prasarana dalam meningkatkan proses pembelajaran di Diniyah Takmiliyah Awwaliyah Al-Fur-qon Desa Paniis terdapat perencanaan, pengorganisasian, pengadaan dan pengawasan. Untuk mengadakan seleksi terhadap barang yang akan dimanfaatkan maksudnya pengelola melakukan pengecekan terhadap barang-barang yang menunjang berjalannya suatu pembelajaran, untuk menghindari kesalahan yang tidak diinginkan.  Upaya Guru yang di lakukan untuk meningkatkan proses pembelajaran peserta didik di Diniyah Takmiliyah Awwaliyah Al-Fur-qon Desa Paniis, hambatan guru dalam meningkatkan proses pembelajaran peserta didik yaitu keterbatasan sarana dan prasarana yang kurang mendukung, permasalahan pada santri juga bisa dilihat dari faktor keluarga nya sendiri, karena kebanyakan dari mereka tidak tinggal dengan orang tua mereka melainkan dengan kakek dan nenek mereka, jadi kurangnya pengawasan dan didikan orang tua nya seperti kedisiplinan santri, sehingga mengakibatkan hambatan-hambatan dalam meningkatkan proses pembelajaran di madrasah.  Faktor pendukung dan penghambat dalam meningkatkan  proses pembelajaran peserta didik di Diniyah Takmiliyah Awwaliyah Al-Fur-qon Desa Paniis, adapun faktor pendukung nya salah satunya pada guru, peran guru lah sangat penting bagi proses pembelajaran, karena keprofesionalitas lah akan menentukan suatu keberhasilan pada saat proses belajar mengajar di dalam kelas. Sedangkan  permasalahan lingkungan dalam  faktor penghambat proses pembelajaran biasanya terjadi pada peserta didik yaitu kurangnya minat santri dalam proses pembelajaran. Hal ini karena ditemukan ada beberapa santri pada saat belajar ada yang masih diluar, ketika di dalam kelas masih ada yang ribut, ada juga santri yang usil dengan teman-teman di dalam kelas. Proses meingkatnya di DTA Al-Furqon bisa dilihat dari peserta didik yang masuk setiap tahunnya bertambah.Kata kunci: Pengelolaan Sarana dan Prasarana, Proses Pembelajaran